Removal of Humic Substances from Drinking Water by Microfiltration, Ultrafiltration, and Nanofiltration membranes (Eurasian Journal of Engineering and Technology, 2023)
In this research, three types of flat sheet membranes were fabricated from polysulfone and N, N diamthelyformamide (DMF) by using wet phase inversion method. Microfiltration (MF), ultrafiltration (UF), and nanofiltration (NF) membranes. The mean pore size diameter of these membranes were calculated which are (0.2 µm, 10 nm and 0.1nm) respectively. The efficiency of membranes was examined to remove humic acid (HA) from synthetic water containing different concentration (3,6,8, and 10 mg/L), and their performances were compared. UV254nm absorbance was used to determine the % of HA compounds eliminated from permeates and retentate samples. To analyze the flux decay and biofouling induced by organic matter, three samples of each membrane were tested using a cross flow filtering system with a single flat sheet membrane. Filtration test of synthetic water containing 8mg/L HA shows removal efficiency 100% for nanofiltration membrane, while ultrafiltration and microfiltration membranes shows removal efficiency 88% and 15% respectively. However, the NF membrane removed 100% of HA and their good efficiency for removing conductivity and turbidity (90, 75%) respectively, but UF membrane is seem to be more convenient from practical point of view, due to their good rejection of HA and turbidity (88% and 70%)) respectively in addition, their good recovery of flux after back washing (88%). The most draw back against NF membrane are their high cost, and high pressure required for operation. Also NF removed the hardness from the water, which are important in proper drinking water quality